PENGARUH MOTIVASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA UKM - Syamsia Ratu Harapan (JURNAL ILMIAH EDUNOMIKA, 2021)
The results of research conducted on 89 informants, namely active students who are members of the Student Activity Unit (UKM) organization at UST. Based on data processing, it is concluded that there is a positive influence of motivation on the performance of SMEs, and organizational commitment also has a positive influence on the performance of SMEs Keywords: Work Motivation; Organizational Commitment; and Performance Of Student Activity Units (UKM);